Platelet rich plasma in dermatology and aesthetic medicine - Neerja Puri (Our Dermatology Online, 2015)
Platelet rich plasma is a promising therapy in dermatology and aesthetic medicine. In this article we will discuss the pros and cons of platelet rich plasma (PRP) and the usage of PRP in aesthetics. PRP is especially used for conditions like facial and neck rejuvenation, fine lines and wrinkles, abdominal striae and facial scarring.